PENCATATAN AKUNTANSI DENGAN SAK EMKM MENGGUNAKAN MS EXCEL PADA TOKO ABC TAHUN 2025 - Sutriyadi, Riko; Octavia, Sindy Nur; Sugiyanto, Eko; Karomah, Nurul Giswi (JURNAL LENTERA AKUNTANSI, 2023)
Accounting is the process of recording or noting a business entity's financial transactions in accounting records, such as journals and ledgers, based on valid transaction evidence. The purpose of accounting is to find out the financial statements at ABC Store. The preparation of ABC Store's financial statements using Microsoft Excel according to needs and to find out the performance results of ABC Store's financial statements. In recording ABC Store's financial transactions from cash receipts and disbursements. Previously, ABC Store only recorded cash receipts and disbursements simply by using paper bookkeeping or bookkeeping. Cash receipt or disbursement transactions are obtained from receipt and purchase transactions at ABC Store and are recorded every day when the total cash receipts or disbursements on that day have been summarized. The weakness is that you have to record one by one in the bookkeeping and calculate manually to find out the total cash receipts each day. The preparation of ABC Store's financial statements using Microsoft Excel is made and explained very well so that the store owner can use it well later. ABC Store knows the difference between before and after the application using Microsoft Excel.